Clinicopathologic and molecular features in hairy cell leukemia-variant: single institutional experience. (November 2018) - Angelova, Evgeniya; Medeiros, L.; Wang, Wei; Muzzafar, Tariq; Lu, Xinyan; Khoury, Joseph; Ravandi, Farhad; Patel, Keyur; Hu, Zhihong; Kanagal-Shamanna, Rashmi
Abstract Hairy cell leukemia-variant is rare. Only a small number of cases have been reported in the literature with little cytogenetic or molecular data available. In this study, we describe the clinicopathologic and genetic features of 23 patients with hairy cell leukemia-variant (16 men and 7 women) with a median age of 70 years. Most patients had splenomegaly (90%), leukocytosis (77%), and lymphocytosis (82%); no patients had monocytopenia. Histologically, the bone marrow biopsy specimens showed a mixed pattern of predominantly interstitial and lesser intrasinusoidal infiltration by leukemic cells. In bone marrow aspirate smears most cells had villous cytoplasmic features and a small nucleolus. We describe unusual sites of hairy cell leukemia-variant involvement in 4 patients, including brain, omentum, terminal ileum, and skin at the time of initial presentation. Immunophenotyping showed monotypic B-cells positive for pan B-cell antigens, CD11c, and CD103, and negative for CD25 and annexin A1. Conventional cytogenetic or fluorescence in situ hybridization analysis showed deletions of 17p13/TP53 and 11q22/ATM gene in 5/12 (42%) and 2/9 (22%) cases, respectively. Sequencing of the variable region ofIGVH showed mutations (>2% deviation from germline) in 40% of the cases assessed.MAP2K1 mutation (p.C121S) was seen in 1 of 14 (7%) patients tested. NoBRAF V600E mutations were detected. The patients were treated in a heterogeneous manner, but most often with therapies designed for classical hairy cell leukemia and the 5-year overall survival was 84%. In summary, hairy cell leukemia-variant exhibits a heterogeneous spectrum of clinical, morphologic, immunophenotypic, and genetic features that may overlap with classic hairy cell leukemia and other hairy cell-like B-cell neoplasms. A subset of patients can have an aggressive clinical course. In our experienceMAP2K1 mutations are uncommon in this disease.